2014
DOI: 10.1111/tpj.12636
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA and degradome profiling reveals a role for miRNAs and their targets in the developing fibers of Gossypium barbadense

Abstract: SUMMARY microRNAs (miRNAs) are 20-24 nucleotide non-coding small RNAs that play important roles in plant development. The stages of cotton fiber development include initiation, elongation, secondary wall thickening (SWT) and maturation. We constructed seven fiber RNA libraries representing the initiation, elongation and SWT stages. In total, 47 conserved miRNA families and seven candidate miRNAs were profiled using small RNA sequencing. Northern blotting and real-time polymerase chain reaction (PCR) analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 57 publications
5
71
0
Order By: Relevance
“…Experiment with soybean seedlings showed that combined application of SNP (as NO donor) and SA alleviated the toxicity of NaCl-induced salt stress by increased proline accumulation and activation of CAT, APX, and GPX. Similar results were reported by Liu et al [96] and Dong et al [97] uptake under salt stress conditions [97].…”
Section: No-phytohormone Cross Talk Under Salinity Stresssupporting
confidence: 81%
“…Experiment with soybean seedlings showed that combined application of SNP (as NO donor) and SA alleviated the toxicity of NaCl-induced salt stress by increased proline accumulation and activation of CAT, APX, and GPX. Similar results were reported by Liu et al [96] and Dong et al [97] uptake under salt stress conditions [97].…”
Section: No-phytohormone Cross Talk Under Salinity Stresssupporting
confidence: 81%
“…The degradome library was constructed as described previously [13]. Poly (A) RNA was extracted from total RNA of mixture of the five samples (1 μg of total RNA for each) using the Oligotex kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…After amplifying 18 PCR cycles, the PCR product was gel-purified for deep sequencing. The sliced miRNA targets were identified according to the CleaveLand pipeline [13]. The potential targets were as followed: alignments with scores less than four (G: U pairs scored 0.5), and no mismatches were found at the site between the 10th and 11th nucleotides of the miRNAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in the understanding of miRNA-mediated gene regulation revealed that miRNAs play important roles in plant developmental switching and plant responses to environmental abiotic and biotic stresses as well as signal transduction (Jones-Rhoades et al, 2006; Li and Zhang, 2016). To date, several studies have investigated many miRNAs and their regulatory functions in the developmental processes of cotton fibers (Wang et al, 2012, 2015; Xue et al, 2013; Liu et al, 2014; Yu et al, 2014; Xie et al, 2015). Both computational prediction and experimental examinations have been widely employed to identify miRNAs in plants.…”
Section: Introductionmentioning
confidence: 99%